Brainstorming Penatalaksanaan Kasus Trauma dan Non Trauma di Sekolah SMK Setia Budhi Rangkasbitung - Purwanto, Ika; S., Maury Cahya; Ningsih, Mutia (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2024)
An accident is an unplanned event that can cause loss of time, property, injury, disability or death. These events can happen anywhere, any time, and can happen to anyone, including in the learning process at school with victim students or anyone at school. For this reason, increasing knowledge for students, especially students who participate in Youth Red Cross (PMR) activities, especially in efforts to provide pre-hospital first aid is very necessary. The purpose of this counseling and training method is that it is hoped that there will be an increase in knowledge between before and after being given counseling, identifying trauma and non-trauma cases in schools, and handling them as well as being able to disseminate the information that has been obtained about the method of carrying out these activities which can be carried out by certified trainers, and pre and post test data were analyzed using paired sample T- test analysis and obtained a significance value of 0.000. This shows that the provision of counseling and simulations related to the management of trauma and non-trauma cases in the general public has a significant effect on the level of student knowledge